An Evaluation of an Online Brief Mindfulness-Based Intervention in Higher Education: A Pilot Conducted at an Australian University and a British University - Chung, Jennifer; Mundy, Matthew Edward; Hunt, Ian; Coxon, Astrid; Dyer, Kyle R.; McKenzie, Stephen (Frontiers in Psychology, 2021)
Mental ill health among higher education students is a well-established problem, therefore it is imperative to implement preventative approaches to support wellbeing. Blended and fully online education programmes widens access for mature or returning students however, the psychological wellbeing of this sub-group of students is under-researched. Finally, evaluating wellbeing interventions that meet the needs of university students as well as accessible for online students, is required. The aim of this study was to evaluate a brief, online, mindfulness-based intervention to assist the self-management of wellbeing and stress for both online and on-campus higher education students. The total sample included 427 participants (96% psychology students) at Monash University, Australia (n = 283) and King’s College London (n = 144), with 152 participants completing the whole study. Participants were allocated to a brief, self-guided, online, mindfulness-based intervention (over the course of one study period) (n = 297), or to a wait-list control group (n = 148). Baseline and end of semester questionnaires included the 14-item Warwick-Edinburgh Mental Wellbeing Scale, 10-item Perceived Stress Scale and the 15-item Mindful Attention Awareness Scale. Regression modelling revealed the intervention condition accounted for up to 12% of the variability in change in student wellbeing, stress and mindfulness between the start and end of semester (when controlling for baseline). These findings support the implementation of a brief, online, asynchronous mindfulness-based intervention for supporting student mental health and psychological wellbeing. An on-going challenge in practice includes engaging and maintaining student engagement in wellbeing initiatives.